2021
DOI: 10.3390/jmse9020131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Factors on the Fishery Catch of the Squid Uroteuthis chinensis in the Pearl River Estuary, China

Abstract: The Pearl River Estuary (PRE) is one of the major fishing grounds for the squid Uroteuthis chinensis. Taking that into consideration, this study analyzes the environmental effects on the spatiotemporal variability of U. chinensis in the PRE, on the basis of the Generalized Additive Model (GAM) and Clustering Fishing Tactics (CFT), using satellite and in situ observations. Results show that 63.1% of the total variation in U. chinensis Catch Per Unit Effort (CPUE) in the PRE could be explained by looking into ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Our data indicated that swordtip squid preferred SSTB ranges of 15-18°C and SST of 24-28°C. Temperature is a dominant factor affecting the distribution of different species of squid (Postuma and Gasalla, 2010;Yu et al, 2015;Yamaguchi et al, 2020a;Fang et al, 2021;Wang et al, 2021;Yamaguchi et al, 2022;Fang et al, 2023;Wang et al, 2023, Yu et al, 2019b and fish (Vayghan et al, 2016;Teng et al, 2021;Mammel et al, FIGURE 5 Correlation between various environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data indicated that swordtip squid preferred SSTB ranges of 15-18°C and SST of 24-28°C. Temperature is a dominant factor affecting the distribution of different species of squid (Postuma and Gasalla, 2010;Yu et al, 2015;Yamaguchi et al, 2020a;Fang et al, 2021;Wang et al, 2021;Yamaguchi et al, 2022;Fang et al, 2023;Wang et al, 2023, Yu et al, 2019b and fish (Vayghan et al, 2016;Teng et al, 2021;Mammel et al, FIGURE 5 Correlation between various environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, temperature changes influence the growth and development of the squid reproductive system (Boavida-Portugal et al, 2010;Wang et al, 2013;Pang et al, 2020). Embryo development, hatching, and juveniles' growth depend on water temperature (Moreno et al, 2012), thus regulating the recruitment capacity of the squid population (Challier et al, 2005) and affecting the CPUE for squid (Wang et al, 2021) and fish stock (Wang et al, 2013;Porcaro et al, 2014). In winter, squid migrates to warmer environments to ensure their feeding and growth in southern Taiwan (Wang et al, 2021;Cheng et al, 2022;Yamaguchi et al, 2022;Fang et al, 2023;Yu et al, 2019c), and this species moves back northward in summer.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, chl-a can be one of the major reference indicators in the analysis of larvae habitat. Studies have shown that the spawning grounds and major fishing grounds of major commercial fishes in the northern SCS may vary with the distribution of chlorophyll concentration [ 51 , 52 ]. This study indicated that the larvae in the PRE inhabited in the waters with Chl-a of 0–10 mg/m 3 , and the optimum Chl-a for larvae in April, June, July, August and September was 2–4 mg/m 3 based on the SI model.…”
Section: Discussionmentioning
confidence: 99%